Under renovation: Large-scale societal events induce shifts between moral ideologies - Yen-Ping Chang; Yu-Shan Chiang; Chun-Kun Wang (PLoS ONE, 2025)
Existing research has revealed various cross-sectional inter-personal/group (e.g., regional) differences in moral traits; it has, however, paid less attention to cross-temporal intra-personal/group moral differences – simply, changes over time. Addressing the intellectual gap, the present research proposes that morality is redefined – renovated – in times when a society undergoes widespread social upheavals, in a manner that the incoming new ideology would better serve the society. Using longitudinal social media (Reddit) text data (N = 459,077,063) from Reddit over the 63 months since the last global great recession starting in late 2007, we report a partial, economy-focused demonstration of the hypothesis, wherein people associated their overall conception of morality more with support for authority and hierarchy and less with fairness and equality when the economic stress was increasing. In comparison, the public reversed the association to lean back on fairness and away from authority when the market was on the rise. Together, the findings offer insights into the communal nature of morality and call for caution that personal moral disposition may be malleable and fluctuating with the collective surroundings, thus cannot be adequately measured without first considering what the disposition means for the cultural-social unity at the moment.